2022
DOI: 10.3389/fimmu.2022.1047922
|View full text |Cite
|
Sign up to set email alerts
|

The CARD8 T60 variant associates with NLRP1 and negatively regulates its activation

Abstract: The NLRP1 inflammasome functions as canonical cytosolic sensor in response to intracellular infections and is implicated in auto-inflammatory diseases. But the regulation and signal transduction mechanisms of NLRP1 are incompletely understood. Here, we show that the T60 variant of CARD8, but not the canonical T48 isoform, negatively regulates the NLRP1 inflammasome activation by directly interacting with the receptor molecule NLRP1 and inhibiting inflammasome assembly. Furthermore, our results suggest that dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…More experiments are required to elucidate the molecular mechanisms underlying the regulation of caspase-1 activation induced by CARD8, as well as the factors influencing the apparent substrate specificity of the protease, which seems to depend on the recruiting inflammasome sensor. The FIIND of CARD8 acts not only as a proteolytic self-activation domain, but can also bind to, and inhibit, the activation of the inflammasome sensors NLRP3, NLRP1, and, possibly, AIM2 [ 89 , 90 ]. Therefore, a crosstalk, mostly mediated through direct interactions, seems to exist between CARD8 and the mentioned inflammasome sensors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…More experiments are required to elucidate the molecular mechanisms underlying the regulation of caspase-1 activation induced by CARD8, as well as the factors influencing the apparent substrate specificity of the protease, which seems to depend on the recruiting inflammasome sensor. The FIIND of CARD8 acts not only as a proteolytic self-activation domain, but can also bind to, and inhibit, the activation of the inflammasome sensors NLRP3, NLRP1, and, possibly, AIM2 [ 89 , 90 ]. Therefore, a crosstalk, mostly mediated through direct interactions, seems to exist between CARD8 and the mentioned inflammasome sensors.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression experiments in HEK293 cells, reconstituted with NLRP1 inflammasome components, demonstrated that CARD8 T60, but not CARD8 T48, binds and inhibits NLRP1 activation [ 90 ]. Expression of T60 in human skin was confirmed at the transcriptional level.…”
Section: Card8 Inhibits Inflammasome Activation and Pro-inflammatory ...mentioning
confidence: 99%
See 3 more Smart Citations